NEURO-IMMUNE MECHANISM OF EPILEPSY AS A KEY TO PATHOGENETIC TREATMENT OF THE DISEASE - L. V. Lipatova (Эпилепсия и пароксизмальные состояния)
Recent studies have proven the functioning of neuro-endocrine and immune systems as a united integrative functional system. This article presents the results of author’s own investigations of clinical neuro-immune disorders in epileptic patients, and the assessment of their role in disease pathogenesis and formation of treatment-resistant forms. A justification of highlyefficient use of immune modulators for treatment of nervous system diseases is presented.